Efecto de un biol elaborado con harinas vegetales y enriquecido con rizobacterias y microalgas en los parámetros morfológicos y productivos de guanábana (Annona muricata L.) en el Pangui, Zamora Chinchipe, Ecuador, - Días Quichimbo, Cristian Javier (2024)
Soursop (Annona muricata L.) is a crop with significant economic potential in Ecuador; however, its yield is often limited in areas that primarily rely on synthetic fertilizer. In this context, the implementation of biofertilizers emerges as a promising alternative to promote more sustainable agriculture. This study evaluated the effect of a biofertilizer (biol) made from plan-based flours and enriched with rhizobateria (Azospirillum and Azotobacter) and microalgae (Chlorella) on the morphological and productive development of the crop in Pangui, Zamora Chinchipe, Ecuador. A completely randomized experimental design was used, consisting of five treatments: T1 (control without biol), T2 (biol from plant-based flours), T3 (biol enriched with rhizobacterial and microalgae), T4, (bio enriched with microalgae), and T5 (bio enriched with both rhizobacteria and microalgae), each with five replicates. Parameters such as plant height, leaf area, chlorophyll content, number of shoots and flower buds, fruit weight, and productivity were measured. The results showed that the combined application of rhizobacteria and microalgae (T5) achieved the best performance across all evaluated variables, reaching a yield of 26.49 tons per hectare. These findings suggest that biol enriched with rhizobacteria and microalgae can enhance the growth and yield of soursop crops, offering a viable alternative for optimizing production sustainably.